2014
DOI: 10.1111/bij.12408
|View full text |Cite
|
Sign up to set email alerts
|

The role of maternal effects in adaptation to different diets

Abstract: The environmental influences of mothers on offspring traits, or maternal effects, often arise from dietary differences experienced by mothers. However, few studies have explored if and how maternal effects facilitate adaptation to new host plants. To address this, we compared the maternal and direct effects arising from dietary differences in two populations of the large milkweed bug, Oncopeltus fasciatus that live on and feed on the seeds from different hosts. We compared a laboratory population, which has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 66 publications
(77 reference statements)
2
24
0
Order By: Relevance
“…; Warner & Lovern ; Newcombe et al . ; Newcombe, Moore & Moore ), while fathers can affect offspring development via proteins and RNA in the sperm and seminal fluid (Wong et al . ; Vojtech et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Warner & Lovern ; Newcombe et al . ; Newcombe, Moore & Moore ), while fathers can affect offspring development via proteins and RNA in the sperm and seminal fluid (Wong et al . ; Vojtech et al .…”
Section: Discussionmentioning
confidence: 99%
“…alternative hosts: see Fox, Waddell & Mousseau ; Newcombe et al . , ; Newcombe, Moore & Moore ), but is problematic in the more typical case where environments vary along a continuous gradient. Like direct effects of environment on phenotype (developmental plasticity), environmentally induced parental effects should generally be viewed as norms of reaction – i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The environments that mothers experience (light, temperature, host and nutrients), together with maternal behaviour (host selection, sexual selection, spawning behaviour and parental care) can affect the phenotypic differences of their offspring (Rossiter, ; Mousseau & Fox, ; Mousseau & Fox, ; Newcombe et al ., ), and this influence is considered a maternal effect. Some parental environmental factors, including temperature, nutrition, photoperiod and population density, could affect offspring phenotypes of insect species (Rossiter, ; Gilchrist & Huey, ; Chen et al ., ; Reznik & Samartsev, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work on the milkweed bug, Oncopeltus fasciatus , has shown that female diet affects offspring fitness through maternal effects (Newcombe et al. ). In addition, maternal effects are known to be of importance in O. fasciatus life history (Groeters and Dingle , ).…”
Section: Introductionmentioning
confidence: 99%
“…The two source populations we studied have different evolutionary histories and are adapted to different diets (Newcombe et al. ). One (Kentucky) is formed of individuals collected from the wild.…”
Section: Introductionmentioning
confidence: 99%